2015
DOI: 10.1371/journal.pone.0124939
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Tissue Derived Stromal Cells in Combination with Hypoxia Effectively Support Ex Vivo Expansion of Cord Blood Haematopoietic Progenitors

Abstract: The optimisation of haematopoietic stem and progenitor cell expansion is on demand in modern cell therapy. In this work, haematopoietic stem/progenitor cells (HSPCs) have been selected from unmanipulated cord blood mononuclear cells (cbMNCs) due to adhesion to human adipose-tissue derived stromal cells (ASCs) under standard (20%) and tissue-related (5%) oxygen. ASCs efficiently maintained viability and supported further HSPC expansion at 20% and 5% O2. During co-culture with ASCs, a new floating population of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 46 publications
(74 reference statements)
2
6
0
1
Order By: Relevance
“…In this study, we found that hypoxia contributed to maintaining the morphology of bBMSCs at passage 10, indicating that hypoxic conditions presented herein suitably replicates in vivo physiology. These results are in agreement with the finding of other researchers who reported the effects of hypoxia on MSCs (Andreeva et al, 2015;Deng et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, we found that hypoxia contributed to maintaining the morphology of bBMSCs at passage 10, indicating that hypoxic conditions presented herein suitably replicates in vivo physiology. These results are in agreement with the finding of other researchers who reported the effects of hypoxia on MSCs (Andreeva et al, 2015;Deng et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…ASCs would support other types of cells (e.g. HSPCs) for their viability and proliferation, through direct/ paracrine cell-to-cell interactions [34,35]. In addition, ASCs can also upregulate the adhesion molecule and extracellular matrix genes in HSPCs, which was good for the latter to anchor and survive in the local area [36].All aforementioned evidence demonstrated that the paracrine factors that secreted by ASCs might be used by CBMNCs for survival and function when they are co-transplanted simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced pH of umbilical cord venous blood is commonly associated with variable degrees of neonatal distress that can include neonatal hypoxia and/ or physiologic stress on the placental vasculature. Hypoxia has been previously associated with hematopoietic progenitor expansion in laboratory studies [13][14][15]. Indeed, the bone marrow stem cell niche is a relatively hypoxic environment [18] and inflammatory cytokines released during physiologic stress [19] or physical exercise [20] and can induce expansion and mobilization of progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, DCC may not be performed in cases associated with infant distress or the need to perform urgent interventions for the baby or mother. The hypoxic stress that is associated with a proportion of such deliveries may actually mobilize greater numbers of stem and progenitor cells [13][14][15]. In this study, we assessed whether specific newborn and maternal factors correlated with indicators of increased blood-forming capacity to inform strategic collection strategies that could augment the quality of units in public cord blood banks.…”
mentioning
confidence: 99%